Tourism Degrowth and Resident Well-being - Dwyer, Larry (Journal of Tourism, Sustainability and Well-being, 2024)
An increasing number of tourism researchers now advance the notion of tourism degrowth as a serious and viable alternative to the mainstream, growth-oriented approach to managing tourism development. The paper seeks to clarify, at a conceptual level, the well-being implications of tourism degrowth, positive and negative. Following a discussion of the basic principles of the degrowth approach, and identification of some major degrowth strategies, the paper overviews the nature of well-being, its sources and indicators. The potential impacts of tourism degrowth on resident well-being, are explored through a lens based on an established well-being framework. Taking sources of both material and non-material well-being into account, it is concluded that the degrowth process, when considered alongside a range of complementary interventions, can potentially make several important contributions to resident well-being. Identification and measurement of resident well-being outcomes in turn provides guidance as to the preferred strategies and types of interventions in support of tourism degrowth. In conclusion, the paper identifies issues for future investigation by tourism researchers.